Construction and Standardization of Scientific Aptitude Test (SAT) for Secondary School Students-A Pilot Study - PandiaVadivu, P; Sridhar, R; Mohan Kumar, B (International Journal of Social Sciences and Management, 2016)
The main objective of the present pilot study was to construct and standardize a Scientific Aptitude Test (SAT) for the secondary school science students (Grade 9 and 10). The test items (30 questions) were prepared by the researchers based on the five important aspects in scientific thinking such as Analogy, Scientific reasoning, Numerical ability, Logical reasoning and Comprehension based questions. A test of multiple choice items were used as a data collection instrument in the six different schools in the selected districts in Tamilnadu, India. The computer based Microsoft excel spreadsheet (2007) was prepared to document the obtained score and the same used for statistical analysis. Through recent method of item analysis, Cronbach’s Alpha values were computed using IBM SPSS software. The reliability coefficients were found 0.874(Spearman-Brown) and 0.672(Guttmann Split-Half). Hence, the present pilot study revealed that the scientific aptitude test for secondary students to ignite their scientific temper and also useful in preparing future competitive examinations. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 17-21